A Savage Conflict : The Decisive Role of Guerrillas in the American Civil War - Sutherland, Daniel E. (Book collections on Project MUSE., 2009)
The American Civil War is famous for epic battles involving massive armies outfitted in blue and gray uniforms, details that characterize conventional warfare. ###A Savage Conflict# is the first work to treat guerrilla warfare as critical to understanding the course and outcome of the Civil War. Daniel Sutherland argues that irregular warfare took a large toll on the Confederate war effort by weakening support for state and national governments and diminishing the trust citizens had in their officials to protect them.